Childhood, youth and activism : demands for rights and justice from young people and their advocates - Wright, Katie; McLeod, Julie (Sociological studies of children and youth, 2023)
In a time of ongoing global instability and the emergence of new fault lines of social inequality generated by the COVID-19 pandemic, the rights of children and young people have been thrown into sharp relief. From uncertain futures arising from the climate crisis to concerns about regressive and reactionary politics to widespread experiences of harassment, abuse and violence, young people and their advocates are mobilising for social change and making their voices heard. Across a variety of topics that engage diverse theoretical perspectives and methodological approaches, Childhood, Youth and Activism: Demands for Rights and Justice from Young People and their Advocates offers a rich exploration of the dynamics between children, youth, activism, and advocacy. The chapters investigate the forms of agency expressed by young people themselves, the hope embodied in social movements, and the centrality of activism and advocacy for creating more hopeful and just futures. Considering the meanings of activism by and for children and young people in the twenty-first century, this edited collection is a valuable resource for scholars, educators and practitioners interested in the intersections of childhood and youth studies, activism and movements for social change.